Antecedents of marketing climate change adaption construction materials: Evidence from Ghana - Kwame Obiri Yeboah; Nicholas Oppong Mensah; Isaac Tandoh; Nana Jesse Telfa Roberts; Kwame Asare Duffour (Economics, Management and Sustainability)
Purpose: Climate Change affects all countries in the world. It impacts negatively on the living conditions of humankind, especially livelihood, temperature change, rainfall regime, and rise in tidal waves. Design/Methodology/Approach: The population in the real estate industry. A descriptive design was used, including questionnaires, to gather data. Since the study sought to examine the willingness to purchase accordingly, a logit regression model was used to predict the likelihood that the dependent variable willingness to pay (WTP) equals 1 (rather than 0). Findings: Income level, price of the products, respondent’s age, gender, and availability of policies concerning eco-friendly products and identified associated health risks positively influence respondents’ WTP. The study reveals that in the real estate sector of the Ghanaian economy, there is a positive WTP eco-friendly roofing product; hence, entrepreneurs and investors should take advantage of the urgency to reduce the impact of climate change in Ghana by investing in eco-friendly products for both the real estate and construction sectors of the economy. Recommendations: The results show that any eco-friendly roof material must raise consumer awareness about the effects of climate change and shape consumer perceptions.